A Legal Review of Corporate Governance Implementation in Developing Countries: A Bibliometric Analysis of Regulatory and Policy Developments - Judijanto, Loso; Purwoto, Ady; Lubis, Arief Fahmi (Westscience Press, 2025)
Corporate governance plays a pivotal role in fostering transparency, accountability, and sustainable economic development, particularly in developing countries. This study conducts a bibliometric analysis using data from Scopus and VOSviewer to explore the academic discourse on corporate governance with a focus on regulatory and policy developments. The analysis reveals